Automation of the logatom intelligibility measurements in rooms - Brachmański, Stefan (Archives of Acoustics, 2007)
Speech intelligibility is one of basic quality parameters of speech transmission in rooms.The methods for assessment of speech quality fall into two classes: subjective and objectivemethods. This paper includes an overview of selected methods of subjective listening measurements(ACR – Absolute Category Rating, DCR – Degradation Category Rating, speechintelligibility) recommended by ITU-T, ISO and Polish Standard and the method of speechtransmission quality evaluation called “modified intelligibility test with forced choice” (MITFC).The MIT-FC method provides fully automatized measurement of speech intelligibilityin rooms. The experiments carried out in finding the relations between logatom intelligibilitymeasured with traditional and theMIT-FC methods for the rooms have shown that there existsthe multivalue and repetitive relation between them.